Postphenomenology and Human Constitutive Technicity: How Advances in AI Challenge Our Self-Understanding - Pavanini, Marco (Journal of Human-Technology Relations, 2024)
In this paper, I aim to assess whether postphenomenology’s ontological framework is suitable for making sense of the most recent technoscientific developments, with special reference to the case of AI-based technologies. First, I will argue that we may feel diminished by those technologies seemingly replicating our higher-order cognitive processes only insofar as we regard technology as playing no role in the constitution of our core features. Secondly, I will highlight the epistemological tension underlying the account of this dynamic submitted by postphenomenology. On the one hand, postphenomenology’s general framework prompts us to conceive of humans and technologies as mutually constituting one another. On the other, the postphenomenological analyses of particular human-technology relations, which Peter-Paul Verbeek calls cyborg relations and hybrid intentionality, seem to postulate the existence of something exclusively human that technology would only subsequently mediate. Thirdly, I will conclude by proposing that postphenomenology could incorporate into its ontology insights coming from other approaches to the study of technology, which I label as human constitutive technicity in the wake of Peter Sloterdijk’s and Bernard Stiegler’s philosophies. By doing so, I believe, postphenomenology could better account for how developments in AI prompt and possibly even force us to revise our self-representation. From this viewpoint, I will advocate for a constitutive role of technology in shaping the human lifeform not only in the phenomenological-existential sense of articulating our relation to the world but also in the onto-anthropological sense of influencing our evolution.